City of Milwaukee: The Collection of Municipal Fees - Berger, Melissa; Collins, Stephen; Fuchs, Patrick; Ley, Emily; Rosen, Lara (My University, 2011)
This report evaluates Milwaukee?s system for collecting municipal fees to help the city address problems related to delayed payment. After examining the collection process across departments and fees, the study quantitatively analyzes factors that may influence initial collection. It determines that certain collection practices -- particularly penalties for late payment -- are strongly associated with timely payment. The authors offer policy options for increasing collection rates and suggestions for further analysis.